An efficient synthetic strategy for ligand-free upconversion nanoparticles. Issue 6 (19th August 2020) - Sun, Chunning; Simke, Jan Ron Justin; Gradzielski, Michael
Abstract : An efficient synthetic approach was developed to prepare ligand-free UCNPs using short-chain acids as stripping agents by a simple vortexing method in a short time, allowing the transfer of UCNPs from hydrophobic to hydrophilic media. Abstract : High-quality lanthanide-doped upconversion nanoparticles are generally synthesized by employing long-chain oleic acid as the ligand in the synthetic process, rendering them hydrophobic, and preferentially dispersed in nonpolar solvents. Thus, postsynthetic surface modifications are required prior to practical applications. Herein, we have developed a facile approach to remove the surface ligand from oleate-stabilized upconversion nanoparticles using short-chain acids as stripping agents by a simple vortexing method on a time scale of 10 seconds. This method allows for the fast and efficient hydrophobic-to-hydrophilic transition in either biphasic solvent systems or single hydrophobic media without any noticeable detrimental effects on size, shape, and phase of crystals during the ligand removal process. Furthermore, the obtained ligand-free upconversion nanoparticles can be readily transferred to the aqueous solution and further modified with water-soluble capping molecules by sequential surface functionalization. As an example, by coupling polymer functionalized upconversion nanoparticles with organic dyes, we are able to construct nanoprobes for selective fluorescence sensing for Cu 2+ .